Knowledge, Attitude and Practice toward Breast Self-Examination among Female Teachers of School at Bharatpur Metropolitan, Chitwan, Nepal - Neupane, Laxmi; Upadhyay, Hari Prasad (Journal of College of Medical Sciences-Nepal, 2025)
Background Breast cancer is the most common cancer among women. In developing countries, breast cancer is diagnosed in late stage. Breast self-examination (BSE) is one of the most important, simple and cost-effective methods for the early detection of breast cancer. The study aims to assess the knowledge, attitude and practice of BSE among female teachers of school. Methods A cross-sectional analytical study was conducted among 100 female teachers in schools of Bharatpur Metropolitan city, Nepal. A non-probability purposive sampling technique was used for data collection. Data was entered and analyzed by using SPSS-20, p-value <0.05 was considered as statistically significant. Results The mean age of the respondents was 33.35 years. Cent percent of the respondents answered that BSE is important for early detection of breast cancer. About 68.0% of the respondents had ever done BSE; among them, 82.35% had done BSE monthly and only 32.35% started BSE in 20 years. of their age. The main reason for not performing BSE was no problem in breast (78.12%). Good knowledge was present in 59.0%, a positive attitude in 73% and a good level of practice present only in 35% of the respondents. No significant association was found between knowledge and practice of BSE with selected demographic variables. A significant association was present between the level of attitude and marital status of the respondents (p=0.017). Conclusions The study concluded that, among school teachers, though knowledge and attitude toward BSE were high, practice was still poor. So, BSE awareness programme focusing on practice is essential.